Penerapan Metode Scrum dalam Pembuatan Sistem Manajemen Sampah Berbasis WEB untuk Meningkatkan Efisiensi Pengelolaan Sampah - Moch Minanur Rahman; Amrullah Amrullah; Muhammad Ainul Yaqin (Department of Science and Technology Ibrahimy University, 2024)
The increase in population, economic capacity, industrial expansion and urbanization have caused significant disruption in waste volumes, which has made traditional waste management systems no longer effective and caused environmental, health and social problems. This research aims to design and implement a web-based waste management system to increase waste management efficiency by applying the Scrum method. Research methods include needs analysis, system design, Scrum implementation, and results evaluation. The Scrum method was chosen because of its focus on collaborative teams and rapid adaptation to change, thus enabling the development of systems that are more responsive to user needs. The research results show that the system developed was successfully implemented well, with all planned features functioning as expected. The conclusion of this research is that applying the Scrum method in developing a web-based waste management system can improve waste management efficiency and coordination. However, further research is needed to optimize this system in real contexts. This research makes an important contribution to the field of waste management by integrating information technology and the Scrum method, and it is hoped that it can become a reference for further research